Cost Volume Profit Analysis of Small Medium Clarias sp. Hatchery Enterprise in Maguan Village, Malang Regency, East Java - Iva Dwi Wulandari; Mimit Primyastanto; Tiwi Nurjannati Utami (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Basori Small Medium Enterprise hasn’t done financial planning yet therefore Basori Small Medium Enterprise need cost volume profit analysis. The aims of the research were to know profile, to analyze cost, sales volume, profit at "Basori" SME in the next period. The type of this research were descriptive qualitative and quantitative. Data collection using observation, interviews, documentation and literature study. The result show that "Basori" SME is a catfish hatchery business located in the village of Maguan, Ngajum subdistict, Malang regency is quite developed. CVP analysis show that the highest cost incurred at Basori SME occurred in the period October - November 2016 amounted to IDR 6,678,656 and the lowest cost occurred in February - March 2018 period of IDR 6,473,656. While the highest seed sales volume was 293,000 seeds in the period of February - March 2018 and the lowest seed sales volume was 234,000 seeds in August - September 2016 period. The highest profit in February - March 2018 was IDR 13,666,344 and the lowest was IDR 11,541,344 in October - November 2016. CVP analysis results are known to forecast sales volume and profits an increase, while costs tend to decrease. Looking at the results of the CVP analysis needs to be done strategic planning to prevent the decline in profits. In this CVP analysis used alternative strategy to increase product sales volume by 2% and reduction of variable cost selected by 5% which will generate profit equal to IDR 115,233,994 with BEP condition at IDR 4,463,340.